IMPROVING TEACHER CREATIVITY THROUGH STRENGTHENING ORGANIZATIONAL CULTURE, INTERPERSONAL COMMUNICATION, PERSONALITY AND WORK ABILITIES IN JAKARTA - Lina Purnama Asih; Thamrin Abdullah; Sri Setianingsih; Soehardi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study aims to analyze to increase creativity through efforts to see the influence of organizational culture, interpersonal communication, teacher personality, and work ability of the teachers of public junior high school (SMPN) in Central Jakarta. The research was conducted during the Covid-19 pandemic in March 2020 to January 2021 with the population of this study were all teachers of public junior high school in Central Jakarta, Indonesia amounting to 1,114 teachers. The selected sample was 243 teachers with the Cochran formula and was taken using proportional random sampling technique. This study uses quantitative research methods with normality, path analysis, T and F tests, and coefficient of determination.The results of this study concluded that organizational culture, intrepersonal communication, personality and abilities significantly influence creativity. Creativity is needed in order to improve the quality of education because creativity is the soul of the development or change and progress of a nation. Education in schools should prioritize efforts to develop creativity, by providing opportunities for the creation of a learning climate that supports the achievement of these goals. The better the organizational culture, teacher personality and work ability where a teacher works that is manifested in innovation and risk taking, attention to detail, results-oriented, human-oriented, team-oriented, aggressive, stable, the higher the teacher's creativity will be. The better a teacher's interpersonal communication which is manifested in the delivery of information, empathy, feedback on the information conveyed, receiving information, effective use of time, and the same perception of the information conveyed, the higher the teacher's work ability.